Kajian Deskriptif Dampak Kerusakan Lingkungan terhadap Rumah Tangga Miskin di Pekanbaru - Putri, Laras Diajeng; Deanda, Vindy Viandra; Taryono (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The sustainability of a society's survival will always depend on its environment. The environment provides beneficial outcomes when managed well; without this management, damage will occur, impacting not only oneself but also the wider community. Pekanbaru has the potential to improve the welfare of its people, but in reality, there are still many poor households that cannot meet their basic needs. The results of this study prove that the Environmental Kuznets Curve (EKC) aligns with the actual conditions of Pekanbaru, and thru a descriptive qualitative analysis approach sourced from the BPS, DLHK, and KLHK institutions/agencies, it can provide explanations for current and future researchers to offer suggestions for government policies. This condition shows that land management in Pekanbaru still needs improvement, and disaster mitigation and post-disaster education must be provided to the community so that they are also aware of the importance of good environmental management, as it will have a negative impact on everyone, especially the income of poor households. Additionally, the government must also create appropriate policies to minimize environmental damage without having to compromise the economies of poor households.